(untitled) (Comparative & International Education Series, 2021)
Global competence refers to ones’ capacity to live and work well in a context that is new to their cultural background (OECD, 2018). However, international students’ dual demands in civic and career global competency has not been conceptually recognized and explicitly addressed in American Higher Education research and practices. This chapter establishes a framework of “unified global competence” aiming to analyze the interactions between civic aspects of global competence (i.e. building critical citizenship) and its career goals (i.e. developing career skill sets). In this framework, three sub-competencies – information, social, and context competence – are identified as important for studying abroad and as reflective for the civic-career interactions. This chapter provides a multidimensional framework for the research and practices on cultivating unified global competencies (not only for a career but also a civic purpose) for international higher education programs.